Simplify Rational Expressions   m-3/3-m

Expert Answers
hala718 eNotes educator| Certified Educator

(m-3)/(3-m)

Let us rewrite 3-m as (-1)(-3+m)

(m-3)/ (-1)(-3+m)

= (m-3)/ (-1)(m-3)

= (-1)*(m-3)/(m-3)

= (-1)*1= -1

neela | Student

To simplify m-3/3-m

Solution:

m-3/3-m= m-1-m = -1 .Where m and -3/3 and -m are treated as 3 distinct terms and each can still be rational expression  m/1 - 3/3 - m/1.  Also following the priority rule of operations . To avoid confusion we should use brackets properly.

(m-3)/(3-m)  and  m-3/3-m are different operation but value is -1 only.